Phylogeny and biogeography of Exacum (Gentianaceae): A disjunctive distribution in the Indian Ocean Basin resulted from long distance dispersal and extensive radiation - Yuan, Yong-Ming; Wohlhauser, Sébastien; Moller, Michael; Klackenberg, Jens; Callmander, Martin; Küpfer, Philippe (My University, 2005)
Disjunctive distributions across paleotropical regions in the Indian Ocean Basin (IOB) often invoke dispersal/vicariance debates. Exacum (Gentianaceae, tribe Exaceae) species are spread around the IOB, in Africa, Madagascar, Socotra, the Arabian peninsula, Sri Lanka, India, the Himalayas, mainland Southeast Asia including southern China and Malaysia, and northern Australia. The distribution of this genus was suggested to be a typical example of vicariance resulting from the breakup of the Gondwanan supercontinent. The molecular phylogeny of Exacion is in principle congruent with morphological conclusions and shows a pattern that resembles a vicariance scenario with rapid divergence among lineages, but our molecular dating analysis demonstrates that the radiation is too recent to be associated with the Gondwanan continental breakup. We used our dating analysis to test the results of DIVA and found that the program predicted impossible vicariance events. Ancestral area reconstruction suggests that Exacum originated in Madagascar, and divergence dating suggests its origin was not before the Eocene. The Madagascan progenitor, the most recent common ancestor of Exacion, colonized Sri Lanka and southern India via long-distance dispersals. This colonizer underwent an extensive range expansion and spread to Socotra-Arabia, northern India, and mainland Southeast Asia in the northern IOB when it was warm and humid in these regions. This widespread common ancestor retreated subsequently from most parts of these regions and survived in isolation in Socotra-Arabia, southern India-Sri Lanka, and perhaps mainland Southeast Asia, possibly as a consequence of drastic climatic changes, particularly the spreading drought during the Neogene. Secondary diversification from these surviving centers and Madagascar resulted in the extant main lineages of the genus. The vicariance-like pattern shown by the phylogeny appears to have resulted from long-distance dispersals followed by extensive range expansion and subsequent fragmentation. The extant African species E. oldenlandioides is confirmed to be recently dispersed from Madagascar.
Keywords: biogeography; DIVA; Exacum; Gentianaceae; ITS; phylogeny; trnL; intron; LENGTH DIFFERENCE TEST; HISTORICAL BIOGEOGRAPHY; SOUTHERN-HEMISPHERE; EURASIA COLLISION; DIVERGENCE TIMES; SEQUENCE DATA; EVOLUTION; INCONGRUENCE; MADAGASCAR; ASIA